2020
DOI: 10.1002/jsfa.10862
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening for hazelnut oil and high‐oleic sunflower oil in extra virgin olive oil using low‐field nuclear magnetic resonance relaxometry and machine learning

Abstract: BACKGROUND As extra virgin olive oil (EVOO) has high commercial value, it is routinely adulterated with other oils. The present study investigated the feasibility of rapidly identifying adulterated EVOO using low‐field nuclear magnetic resonance (LF‐NMR) relaxometry and machine learning approaches (decision tree, K‐nearest neighbor, linear discriminant analysis, support vector machines and convolutional neural network (CNN)). RESULTS LF‐NMR spectroscopy effectively distinguished pure EVOO from that which was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 36 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Similarly, Zhu et al [ 23 ] applied discriminant analysis (DA) for estimating the adulteration ratios of peanut oil adulterated with soybean oil, rapeseed oil, or palm oil based on LF-NMR relaxometry measurements. The accuracy of edible oil adulteration detection and analysis based on these LF-NMR relaxometry techniques has been further enhanced by applying machine learning algorithms, such as support vector machine (SVM) [ 24 ], convolutional neural network (CNN) [ 25 ], and combined SVM and CNN machine learning approaches [ 26 ]. These studies have demonstrated the substantial potential for applying LF-NMR relaxometry for the rapid identification of oil adulteration.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Zhu et al [ 23 ] applied discriminant analysis (DA) for estimating the adulteration ratios of peanut oil adulterated with soybean oil, rapeseed oil, or palm oil based on LF-NMR relaxometry measurements. The accuracy of edible oil adulteration detection and analysis based on these LF-NMR relaxometry techniques has been further enhanced by applying machine learning algorithms, such as support vector machine (SVM) [ 24 ], convolutional neural network (CNN) [ 25 ], and combined SVM and CNN machine learning approaches [ 26 ]. These studies have demonstrated the substantial potential for applying LF-NMR relaxometry for the rapid identification of oil adulteration.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the CVM achieved 84.92% accuracy, 54 while the convolutional neural network (CNN) algorithm had an accuracy of 89.29%, a precision of 81.25%, and a recall of 81.25% and enabled the rapid discrimination of pure EVOO from the counterparts adulterated with hazelnut or high-oleic sunflower oils in the range of 10−100% (v/v) in 2 min. 55 ■ OTHER DETECTION TECHNIQUES…”
Section: ■ Spectroscopic Fingerprinting Techniquesmentioning
confidence: 99%
“…Combined with chemometric spectrum methods, FTIR and Raman spectroscopy can be used to detect the adulteration of EVOO with high accuracy. [21][22][23][24][25] Other spectroscopic methods have been developed, for instance, Fluorescence spectroscopy, [26,27] Nuclear magnetic resonance (NMR) analysis, [28] Low-field NMR, [29] Nonthermal plasma used to induce the detectable oxidation products. [30] Other works employed determination of carbon stable isotopes, [31] detection of DNA and metabolite-based markers, [32,33] and dielectric spectroscopy.…”
Section: Introductionmentioning
confidence: 99%